The role of e-learning in developing the university education environment in institutes of science and technology of physical and sports activities (A field study on the professors of the Institute of Sciences and Techniques of Physical and Sports Activit - بطاط نورالدين (sports creativity, 2025)
This study aims to identify the role of e-learning in developing the university education environment in institutes of science and technology of physical and sports activities, according to the following variables (department, teaching experience, place of residence). The study sample consisted of (15) professors, or 15%. The results of the study concluded that e-education has a role in developing the university education environment in the institutes of science and technology of physical and sports activities from the point of view of the faculty members, and that there are no statistically significant differences in the viewpoint of faculty members about the role of e-learning in developing the university education environment in the institutes of science and technology. Physical and sports activities according to the variables (department, teaching experience, place of residence)